(untitled) (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
The main objective of this study is to improve productivity of the rolling mill of the steel plant by implementing Total Productive Maintenance (TPM). Due to the increasing demand of steel products, it is necessary to improve productivity of the rolling mill as various types of structural items are produced by rolling mills. Machine maintenance plays an important role in achieving maximum production in steel industry. The TPM was implemented in an integrated steel plant and its effect on output was observed. The TPM was implemented in an integrated steel plant. First, six months of data were collected, and then the breakdowns were analyzed using TPM. Then, TPM was implemented for the next six months and the productivity of the rolling mill was analyzed. The productivity of the rolling mill was enhanced by 10% by implementing TPM, and equipment availability was also improved by about 14%. However, after the implementation of TPM, the overall equipment efficiency (OEE) reached about 80.19%, which is close to the world steel OEE of 85%.